IMPLEMENTASI PERATURAN BUPATI MOJOKERTO NOMOR 27 TAHUN 2021 DALAM RANGKA PENGELOLAAN ALOKASI DANA DESA (Kecamatan Pungging Kabupaten Mojokerto) - Indrayana, Samuel; Kurniawan, Bagus Ananda; Azizah, Anisa Kurniatul (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
Allocation of Village Funds is a balance of central and regional financial funds received by the Regency/City which in distribution is distributed to each village, namely at least 10% (ten percent). The purpose of this study is to find out the implementation of Mojokerto Regent Regulation Number 27 of 2021 concerning Guidelines for Implementation of Village Fund Allocation (ADD) in Pungging District, Mojokerto Regency, as well as to find out what factors influence the implementation of the Mojokerto Regent's policy Number 27 of 2021. . This writing describes and knows the problems being studied in this case, namely the evaluation of the Mojokerto Regency Regulation No. 27 of 2015 in the context of managing Village Fund Allocations. This study uses a descriptive qualitative method, which describes the management of Village Fund Allocations in Pungging District, Mojokerto Regency. By using data collection techniques through interviews with informants regarding the implementation of Village Fund Allocations, then comparing it with Mojokerto Regent Regulation Number 27 of 2021 concerning Guidelines for Implementing Village Fund Allocations. Several factors influence the implementation of Village Fund Allocation management in Pungging District, Mojokerto Regency, including internal factors, namely Executors, Mojokerto Regency Regulation No. 27 of 2021, Government Officials and external factors, namely Social, Political and Economic conditions.Â Keywords: Policy Implementation, Mojokerto Regency Regulation No. 27 of 2021. Allocation of Village Funds.